In-situ lignin sulfonation for enhancing enzymatic hydrolysis of poplar using mild organic solvent pretreatment. (February 2023) - Wu, Ruijie; Li, Yongzheng; Wang, Xiaodi; Fu, Yingjuan; Qin, Menghua; Zhang, Yongchao
Graphical abstract: Highlights: Poplar was pretreated by reusable organic solvent under mild temperature (≤100 °C). Almost all hemicelluloses and part of lignin was extracted with cellulose retained. Sulfonic acid groups were introduced into lignin structure remained in substrates. 89% improved glucose conversion compared with that of non-sulfonated substance. New strategy is exploited to realize sulfonation and promote biomass bioconversion. Abstract: Biomass pretreatment is an essential strategy to overcome biomass recalcitrance and promote lignocellulosic bioconversion. Here, a reusable organic solvent system (formic acid-methanesulfonic acid) was explored to pretreat poplar under a mild temperature (below 100 °C). The results showed that the co-solvent system could extract basically complete hemicelluloses and part of lignin with original cellulose retained in the pretreated substrates. Meanwhile, sulfonic acid groups were introduced into lignin structure remained in the substrates. The glucose conversion yield of the substrates with a higher concentration of sulfonic acid groups (13.2 mmol/kg) reached 45.9 % by reducing the hydrophobic interaction between lignin and cellulase, showing 89.3 % improvement compared with that of the substrates treated with single formic acid. This progressive study aimed to develop a new strategy to realize sulfonation and promote enzymatic hydrolysis of substrates by using mild organic solvent pretreatment.